Lung Ultrasound for the Diagnosis and Management of Neonatal Respiratory Distress Syndrome: A Minireview - Guo, Bin-Bin; Pang, Lin; Yang, Bo; Zhang, Cong; Chen, Xiao-Ya; OuYang, Jia-Bao; Wu, Chang-Jun (Frontiers in Pediatrics, 2022)
Lung ultrasound is useful for diagnosis of respiratory distress syndrome in neonates. Recently, it has been proved to play an important role in management of neonatal respiratory distress syndrome (RDS). It is feasible to grade RDS and select therapeutic modalities accordingly by LUS. The treatment also should be adjusted with the change of ultrasound images. In conclusion, LUS is valuable for the diagnosis and management of neonatal respiratory distress syndrome.